Is computerised tomography better than fibreoptic gastroscopy for early detection of gastric varices? - Suvak, Burak; Kekilli, Murat; Beyazit, Yavuz; Okten, Sarper; Tanoglu, Alpaslan; Sasmaz, Nurgul (Gastroenterology Review/Przegląd Gastroenterologiczny, 2017)
Introduction : Video endoscopic diagnosis of gastric varices is particularly limited, owing to the deep submucosal or subserosal location of the varices and the normal appearance of the overlying mucosa. Aim: We present and emphasise the value of computerised tomography (CT) examination in the early detection of gastric varices (GVs). Material and methods : In this retrospective study, a total of 216 consecutive patients with cirrhosis were evaluated at the Turkiye Yuksek Ihtisas Training and Research Hospital between September 2008 and March 2011. Results : One hundred and thirty patients with cirrhosis were enrolled in the study. The mean age of the male (88 cases) patients was 59.45 ±2.42 years, and the mean age of the female (42 cases) patients was 56.29 ±1.14 years. Computerised tomography identified oesophageal varices (EVs) in 103/130 patients, and endoscopy identified EVs in 103/130 patients. Computerised tomography identified GVs in 86/130 patients, and endoscopy identified GVs in 26/130 patients. After endoscopic elastic band ligation (EBL), CT identified GVs in 22/26 patients, and endoscopy identified GVs in 7/26 patients. Conclusions : Gastric varices lie in the submucosa, deeper than EVs, and distinguishing GVs from gastric rugae may be difﬁcult with video endoscopy. This study demonstrated that CT is a sensitive method for early detection of GVs and has been used previously in the evaluation of GVs.